Pomen meta-vizije Sodišča Evropske unije za Slovenijo - Kukovec, Damjan (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
The author examines how the concept of autonomy of EU law, which represents the organisational principle of the coherence of the CJEU, ensuring the unity and coherence of the European legal system and permeating the entire case law of the CJEU, has played a key role in high-profile cases before the CJEU in which Slovenia was directly involved. The author first discusses the Detiček case, the first Slovenian reference for a preliminary ruling, in which the Court of Justice addressed a controversial area of intersection of the principle of mutual trust and the protection of human rights, key elements of autonomy. In the second case concerning the archives of the Slovenian central bank, the Commission sought a declaration that Slovenia had violated the inviolability of EU archives, and thus the autonomy of the European institutions and the autonomous implementation of EU law, by unilaterally seizing documents from the Bank of Slovenia headquarters. In the third case, Slovenia v Croatia, the Court found that it did not have jurisdiction to determine whether Croatia had violated EU law by failing to enforce an arbitral award because the arbitration agreement never became part of the EU legal order. The author concludes that a deeper understanding of the role of autonomy in the CJEU’s legal reasoning could enable Slovenian lawyers to better predict the Court’s decisions, and thus to better articulate Slovenia’s interests in the language of EU law.
Keywords: človekove pravice; Evropska unija; pravni sistemi; pravo; Slovenija; Sodišče Evropske unije